Chief of Residents for Quality Improvement and Patient Safety: A Recipe for a New Role in Graduate Medical Education. Issue 3 (1st March 2017) - Ferraro, Kelly; Zernzach, Randall; Maturo, Stephen; Nagy, Christopher; Barrett, Rebecca
ABSTRACT: Introduction: The San Antonio Uniformed Services Health Education Consortium (SAUSHEC) is the largest group of residency programs in the Department of Defense. In an effort to provide improved Quality Improvement and Patient Safety (QI/PS) training for its residents, SAUSHEC created the position of Chief of QI/PS for Residents in the academic year 2014–2015. The Chief of QI/PS for Residents was based in the Internal Medicine residency program but also assisted with SAUSHEC-wide QI/PS projects. This is the first such job in the Department of Defense. Methods: Here, we detail the accomplishments during this first academic year, including the alignment of the job with the stated QI/PS-related goals of the Accreditation Council for Graduate Medical Education Clinical Learning Environment Review. Efforts focused within the Internal Medicine residency program included QI/PS curriculum development, improvement upon monthly morbidity and mortality (M&M) conferences, and facilitating resident participation in QI projects. The 2014–2015 academic year Internal Medicine residency QI/PS project focused on increasing comfort and discussions with patients regarding advance directives; this also served to emphasize the humanistic side of potential QI/PS projects. The Chief of QI/PS for Residents also spearheaded hospital-wide initiatives, including the creation of a quarterly hospital-wide M&M conference, coordinating resident involvement in QI/PS-related committees, and facilitating feedback of patient safety report responses to trainees. Results: We focus on the portion of the QI/PS curriculum involving the presentation of a mock Root Cause Analysis (RCA) and provide the results of a pre- and postpresentation survey of resident knowledge of RCAs. In order to quantify the efforts over the entire academic year, we also report the results of a resident self-assessment of QI/PS aptitude and competencies, including changes in these measures over the academic year. Finally, we discuss challenges faced and outline future goals for the position. Conclusion: The SAUSHEC Chief of QI/PS for Residents is the first such designated position in the Department of Defense. As QI/PS continues to increase as a focus area for physician training, we anticipate that other programs will create similar positions. We provide ideas for how a Chief of QI/PS for Residents can be involved at a program and hospital-wide level and quantify the success of different efforts.